Bromocriptine for Idiopathic Intracranial Hypertension: A Retrospective Multicenter Cohort Study - Morsy MM; Azzam AY; Mirdad MT; Abadi AM; Alqahtani SAM; Abukhadijah HJ; Elamin O; Morsy MD; Altschul DJ (International Journal of General Medicine)
Mahmoud M Morsy,1,* Ahmed Y Azzam,1,* Mohammed Tarek Mirdad,2 Alsaleem Mohammed Abadi,3 Saif Aboud M Alqahtani,4 Hana J Abukhadijah,5 Osman Elamin,6 Mohamed D Morsy,7 David J Altschul8,9 1October 6 University Hospital, October 6 University, Giza, Egypt; 2College of Medicine, King Khalid University, Abha, Saudi Arabia; 3Family and Community Medicine Department, College of Medicine, King Khalid University, Abha, Saudi Arabia; 4Internal Medicine Department, College of Medicine, King Khalid University, Abha, Saudi Arabia; 5Medical Research Center, Hamad Medical Corporation, Doha, Qatar; 6Department of Jordan Hospital Neurosurgery, Amman, Jordan; 7Department of Clinical Physiology, College of Medicine, King Khalid University, Abha, Saudi Arabia; 8Montefiore-Einstein Cerebrovascular Research Lab, Montefiore Medical Center, Albert Einstein College of Medicine, Bronx, NY, USA; 9Department of Neurological Surgery, Montefiore Medical Center, Albert Einstein College of Medicine, Bronx, NY, USA*These authors contributed equally to this workCorrespondence: David J Altschul, Department of Neurological Surgery, Montefiore Medical Center, Albert Einstein College of Medicine, Bronx, NY, 10467, USA, Email daltschu@montefiore.orgIntroduction: Idiopathic Intracranial Hypertension (IIH) is a disorder characterized by elevated intracranial pressure without an identifiable cause, commonly affecting young obese women. Current treatment strategies, including weight loss, acetazolamide, and surgical interventions, have limitations due to side effects, adherence challenges, and potential complications. Bromocriptine, a dopamine D2 receptor agonist, has emerged as a potential novel therapy due to its metabolic effects. This study aims to evaluate the safety and efficacy of bromocriptine in IIH management through a retrospective cohort analysis.Methods: A retrospective analysis was conducted, focusing on patients with IIH. Propensity score matching was applied to balance baseline characteristics, including age, sex, race, and BMI, between the bromocriptine and control groups. Key outcome measures, papilledema, headache severity, refractory IIH status, and acetazolamide dose dependency, were assessed at multiple follow-up intervals.Results: The bromocriptine group demonstrated significant improvement in papilledema and headache severity over 24 months, with early effects observed at one month. There was a marked reduction in refractory IIH (30.66% lower incidence at 24 months, p< 0.0001) and reduced dependency on acetazolamide from three months onward (p=0.0246). The safety profile was favorable, with comparable adverse event rates to controls, although allergic skin reactions were noted in the bromocriptine group.Conclusion: Bromocriptine shows promise as an effective and safe therapeutic option for IIH, with sustained improvement in clinical parameters and reduced reliance on conventional treatment. Future randomized controlled trials are needed to confirm these findings and explore optimal dosing strategies.Keywords: idiopathic intracranial hypertension, pseudotumor cerebri, intracranial pressure, bromocriptine, dopamine